Self-esteem as a risk factor of anxiety in senior high school students - Pratama, Yoga Rizky; Tjhin, Purnamawati (Faculty of Medicine, Universitas Trisakti, 2024)
BackgroundAdolescence is a dynamic period of significant physical, emotional, and cognitive development, where individuals shape their identities and influence their mental health. Being vulnerable to various risk factors, including anxiety, adolescents often face mental disorders that can affect their overall well-being. With anxiety being a major concern in the global context as well as in Indonesia, this study aimed to determine self-esteem as a risk factor of developing anxiety among senior high school students. MethodsA cross-sectional study was conducted involving 162 senior high school students, using proportionate stratified cluster simple random sampling. Data were collected through the Rosenberg Self Esteem Scale and the Hamilton Anxiety Rating Scale questionnaires to measure self-esteem and anxiety levels, respectively. The full score for self-esteem was 10–40 points. The higher the score, the greater the self-esteem. Data was analyzed using multiple logistic regression. ResultsThe research findings indicate that adolescents experiencing anxiety amount to 51.9% and most of them indicated high self-esteem (61.1%). Multiple logistic regression test showed that low self-esteem (OR=2.21; 95% CI: 1.15-4.24) was the most influential risk factor of anxiety. However, there were no significant associations between anxiety and demographic factors such as gender, grade level, major of study, and parental income. ConclusionMost senior high school students experience anxiety, and lower self-esteem was the most influential risk factor of anxiety. The findings highlight the need for targeted interventions to boost self-esteem as a preventive measure against anxiety among senior high school students.